EDUCATIONAL VALUES IN THE NOVEL ENTITLED NEGERI 5 MENARA BY A. FUADI - Ramlah; M. Amir P; Indriati Lewa (International Journal of Social Science, 2022)
The objective of this study was to explain the educational values ​​in the novel Negeri 5 Menara by A. Fuadi. This was a descriptive qualitative study to describe the explicit and implicit educational values ​​in the novel Negeri 5 Menara by A. Fuadi. In the implementation of this research design, the researcher firstly collected data, processed, and analyzed the data. The results showed that the educational values ​​in the novel Negeri 5 Menara by A. Fuadi, namely: (1) Divine values ​​include faith in Allah, faith in prophets and apostles, faith in the holy book, and faith in the hereafter; (2) Moral values ​​include giving advice, loving children, filial piety to parents, responsibility, being diligent, disciplined, respecting, not giving up easily, loving the homeland, keeping promises, being sincere, and being high-minded; (3) Social values ​​include sympathy, sharing, friendship, and a sense of kinship; (4) Cultural values ​​include love of local products, pride in their mother tongue, preserving local arts, caring for traditional houses, appreciating special foods, trading systems, pesantren culture, campus culture, and livelihood system; and (5) Aesthetic values ​​include the style of rhetorical questions, figurative language styles, and rhymes.